2007
DOI: 10.1089/pho.2007.2076
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 780-nm Laser Phototherapy on Peripheral Nerve Regeneration after Neurotube Reconstruction Procedure (Double-Blind Randomized Study)

Abstract: The results of this study suggest that postoperative 780-nm laser phototherapy enhances the regenerative process of the peripheral nerve after reconnection of the nerve defect using a PGA neurotube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(59 citation statements)
references
References 29 publications
2
50
0
7
Order By: Relevance
“…In the treatment of peripheral nerve injuries, suturing with vinyl and silk was done first; however in light of the number of sutures and the negative effects of the sutures on recovery, fibrin glue and wrapping the injured nerve were also tried. Electrical stimulation, therapeutic ultrasound, low-dose radiation, and low-intensity laser were also tested in experimental models to produce nerve regeneration and functional recovery (8,13,15,16,17).…”
Section: I-light Microscopic Evaluationmentioning
confidence: 99%
“…In the treatment of peripheral nerve injuries, suturing with vinyl and silk was done first; however in light of the number of sutures and the negative effects of the sutures on recovery, fibrin glue and wrapping the injured nerve were also tried. Electrical stimulation, therapeutic ultrasound, low-dose radiation, and low-intensity laser were also tested in experimental models to produce nerve regeneration and functional recovery (8,13,15,16,17).…”
Section: I-light Microscopic Evaluationmentioning
confidence: 99%
“…[26][27][28] Most reports on the effect of LLLT on PNS injury are in cases of axonotmesis. [13][14][15][18][19][20][21]25,[29][30][31][32] However, promising results have been obtained in severe cases of neurotmesis when LLLT is used in combination with or Gore-Tex tubes. 27 The cutaneous branch consisted of 400 myelinated and 1800 unmyelinated afferent axons.…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal management often includes antidepressants but, as studied by Tammialia-Salonen et al antidepressants did not effectively relieve BMS associated symptoms 29 . Effectiveness of LLLT in peripheral nerve regeneration was demonstrated in several studies [30][31][32] . Nerve regeneration and acceleration of axonal growth was observed in rats after the application of 780 nm laser 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Effectiveness of LLLT in peripheral nerve regeneration was demonstrated in several studies [30][31][32] . Nerve regeneration and acceleration of axonal growth was observed in rats after the application of 780 nm laser 30 . In another study, rabbits who were treated with 901 nm laser showed thicker nerve fibers, clearer Ranvier nodes and more regular myelin layers, compared to control group 31 .…”
Section: Discussionmentioning
confidence: 99%